Selections from 90 minutes in heaven : an inspiring story of life beyond death - Piper, Don, 1950- (Revell, 2008)
"Excerpted from the bestseller, "90 Minutes in Heaven" this ... edition focuses on the reality of Piper's heavenly experience"--P. [4] cover.